New Aramaic Papyri from Elephantine in Berlin - Moore, James D. (Brill, 2022)
The famous German excavations between 1906 and 1908 of Elephantine Island in Egypt produced some of the most important Aramaic sources for understanding the history of Judeans and Arameans living in 5th century BCE Egypt under Persian occupation. Unknown to the world, many papyri fragments from those excavations remained uncatalogued in the Berlin Museum. In New Aramaic Papyri from Elephantine in Berlin James D. Moore edits the remaining legible Aramaic fragments, which belong to letters, contracts, and administrative texts.